Association between metabolic dysfunction-associated steatotic liver disease and kidney stone risk in individuals with metabolic dysfunction: evidence from cross-sectional and cohort analyses - Wei, Yushuang; Ye, Lingyu; Li, Mingli; Yan, Boteng; Lin, Yining; Lai, Sihua; Mo, Zengnan; Tang, Chaoyan (Frontiers in Endocrinology, 2026)
IntroductionKidney stones are a common disorder with increasing global prevalence. Metabolic dysfunction-associated steatotic liver disease (MASLD), a systemic metabolic condition, has been suggested to be linked with kidney stones, but existing evidence is inconsistent. This study aimed to clarify the association between MASLD and kidney stones risk using both cross-sectional and cohort analyses.MethodsA total of 1,875 participants from a cross-sectional study and 1,903 from a community-based cohort were analyzed. Logistic regression was used in the cross-sectional study, while incidence rates, Kaplan–Meier curves, log-rank tests, and Cox models estimated risk in the cohort. Subgroup and mediation analyses were performed, with METS-IR, WBC, and eGFR examined as mediators.ResultsIn the cohort study, there were 94 incident kidney stone cases identified during a median follow-up of 34.62 months, with an incidence rate of 17.6 per 1,000 person-years. In the cross-sectional analysis, MASLD was positively associated with kidney stones, with an odds ratio (OR) of 1.466 (95% CI: 1.059–2.028) after adjustment for potential confounders. Kaplan–Meier analysis revealed significant differences in cumulative incidence between MASLD and non-MASLD groups (log-rank P < 0.001). Cox regression confirmed MASLD as an independent risk factor for kidney stones (HR = 2.04, 95% CI: 1.29–3.23). Subgroup analyses showed consistent associations in metabolically high-risk individuals. Mediation analyses further highlighted METS-IR as a key mediator linking MASLD to kidney stone formation.ConclusionsMASLD was independently associated with increased kidney stone risk, particularly in metabolically high-risk individuals. METS-IR mediated this relationship, underscoring the critical role of insulin resistance.